FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN PERILAKU SEKSUAL REMAJA YANG TINGGAL DI LINGKUNGAN RESOSIALISASI ARGOREJO KOTA SEMARANG - Putri, Shieldine; Shaluhiyah, Zahroh; Prabamurti, Priyadi Nugraha (Fakultas Kesehatan Masyarakat, 2017)
A teenager is potentially at risk groups and needs serious attention and one of them about sexuality is considered a major problem in the development of life. Teen living surroundings resocialization are often exposed by various activities of prostitution. This research aims to analyze the sexual behavior of teens who live in the Argorejo Resocialization environment. This research used a cross-sectional study design. The population in this research as much as 63 respondents with total sampling technique for quantitative and 5 informants with purposive sampling for qualitative. The instrument used was a questionnaire and in-depth interview. This research use univariate and bivariate analysis.The results showed that more than half of respondents are male (60,3 %). Most respondents are in the age 17-25 years (52, %), low educated ≤SMA (92,1 %), it does not work (76,2 %), parents work as self-employed (39,7 %), and status of residence along with parent (90,5 %). Amount (11,1 %) of respondents behave very risky sexual. The chi square test showed that the work of respondents (p=0.000), attitude to sexual behavior (p=0.011) and behaviour of peers (p=0.035) are significantly related to adolescents sexual behavior. While the variables of gender, age, level of education, the status of residence, parents work, knowledge of sexual behaviour, parents support and support health workers are not significantly related to adolescents sexual behaviour. From the qualitative research results obtained that two of the three informants did not use a condom during inercourse his sexual behavior is very risky. Future expected to reactivate teenagers group and formed the PIK-R.